2013
DOI: 10.7874/kja.2013.17.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Metastasis of Gastric Carcinoma to the Cerebellopontine Angle

Abstract: Internal auditory canal (IAC) and cerebellopontine metastases are very rare lesions and their diagnosis is very difficult due to their similarity to vestibular schwannoma in clinical characteristics and radiologic findings. Our case is peculiar and differs from previously reported cases of malignant metastasis to the IAC in two aspects: 1) solitary IAC metastasis occurred without distant metastasis and 2) symptoms due to IAC metastasis preceded outbreak of primary lesion symptoms or diagnosis of primary lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In this study, a review of the literature from PubMed revealed only six cases of CPA metastasis from gastric tumors (►Table 1). [4][5][6][7][8][9] Although it is rare, metastatic brain tumors in CPA should not be followed up as benign tumors, and it is important to distinguish them carefully. It is useful to focus on the clinical symptoms and neuroimaging findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a review of the literature from PubMed revealed only six cases of CPA metastasis from gastric tumors (►Table 1). [4][5][6][7][8][9] Although it is rare, metastatic brain tumors in CPA should not be followed up as benign tumors, and it is important to distinguish them carefully. It is useful to focus on the clinical symptoms and neuroimaging findings.…”
Section: Discussionmentioning
confidence: 99%